AJIAN PUPUK ORGANIK CAIR LENGKAP DOSIS RENDAH PADA SISTEM BUDIDAYA TANPA OLAH TANAH TERHADAP PERTUMBUHAN GULMA DAN HASIL JAGUNG - Ichwan S. Madauna (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The research aim was to identify the effect of liquid organic fertilizer at low dosage on weeds growth and corn yield in no tillage agriculture. The research was conducted in farmer’s land in Donggala Regency, and in the laboratory of agricultural Faculty of  Tadulako University from May 2007 to  September 2007. The research used a Randomized Block Design in a Factorial experiment with three replicates.  Two factors applied were no tillage agriculture and complete liquid fertilizer. The first factor included no tillage (TOT), TOT + mulch, TOT + glysofat, and TOT+mulch+glysofat.  The second factor consisted of no fertilizer, complete liquid fertilizer at 1/3 recommended dosage (1 L ha-1), complete liquid fertilizer at 2/3 recommended dosage (2 L ha-1), and complete liquid fertilizer at equal to recommended dosage (3 L ha-1).  The research results showed that there was no interaction effect on weeds dry weight ha-1, dry kernel yield ha-1, 100 kernel weight, kernel number per cob, and cob length.  The NJD of weeds changed from broad leave weeds group of  Alternanthera sessilis (L.) DC to teky weeds of  Cyperus rotundus L. The no tillage+mulch+ glisofat treatment resulted in the lowest weeds dry weight of 20.556 g, the highest dry kernel yield of 4,338 ton ha-1, and 100 kernel weight of 34.876 g.